As áreas de endemismo dos opiliones (arachnida) da floresta atlântica ao norte do rio São Francisco, Brasil - Souza, Adriano Medeiros de (2013)
The Atlantic Forest is one of the richest regions of the world, both in species diversity, as in endemism. Due to this and to the degree of devastation, a few years ago, this biome was considered one of the 25 worldwide biodiversity hotspots. However, the historical relationships between different sectors of the Atlantic Forest are poorly understood. A critical step in that knowledge is the delimitation of the areas of endemism, which are basic units for biogeographic analyzes. Studies performed in this subject have advanced enough, both south and southeastern Atlantic Forest, by using the distribution patterns of harvestmen which occur into this region, nevertheless, a gap remains regarding to the northeastern Atlantic Forest. Therefore, this study aims to delimit the areas of endemism in Atlantic Forest north São Francisco river, by using Opiliones species distributions, also comparing the obtained results by different methodologies and finally evaluating the influence of the size of the cells on the results. In total, we used 1581 occurrences of 224 species, and of these, 18 are not yet described. The occurrences were obtained of field collecting, literature and museums. We used three numeric methods to search for areas of endemism that work using the occurrence of species in a set of cells on a grid: Endemicity Analysis (NDM), Parsimony Analysis of Endemicity (PAE) and Biotic Element Analysis (BEA). For the three methods were applied three grids: a less detailed grid (2° X 2°), a intermediated grid (1° X 1°) and one more detailed grid (with 0,5° X 0,5° cells). Afterwards, the areas of endemism were delimited by applying on the results of the numeric analyzes a protocol based on a number of combined criteria derived from areas of endemic concepts described in the literature. Altogether, thirteen endemism areas were delimited for Atlantic Forest, and, three of these correspond to the northeastern Atlantic Forest: Area of Endemism Bahia (BA), Area of Endemism Brejos Cearenses (BCE) and Area of Endemism Pernambuco (PE). The results from NDM and PAE were similar, whereas BEA results were entirely different and arbitrary. The size of cells had influences in the analysis, both on the number of areas found, as the number of cells included in each area. The largest amount of data used, turned limited areas into more robust, especially those of the northeastern Atlantic Forest, if compared to previous work. These areas, as well as those from south and southeastern Atlantic Forest probably correspond to areas of Pleistocene forest refuge, when the entire Atlantic Forest experienced cycles of expansion and contraction. These oscillations are associated with the cycles of glaciation and warming that occurred during the Quaternary, where, the expansion of northeastern Atlantic Forest boundaries probably led it to a contact with the Amazon Rainforest. Other likely causes were marine transgressions or tectonism, in this case, applied to the region of Baía de Todos os Santos.